(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Mental Health of children and teenagers is an important component of their physical health and developmental process and as such its increasing relevance is getting concern around the globe. The current period is a witness to a dramatic shift in socio-cultural and economic paradigm owing to globalization and dramatic technical development. The increased sophistication of our social and economic growth has made the life quick, dynamic and competitive. The children of today are not out of the impacts of this dramatic transition. This has accelerated stress on the children for their high accomplishments to brace for the future keeping pace with the demand of the globalized world giving rise to Mental Wellbeing issue in children and adolescents. This is ultimately impacting their academic performance because Mental Wellbeing and well-being are a necessity for going to academic progress and as such mental health issues become an obstacle to learning of the students. Children and youth are the important components of human capital of a community. This time is the beginning of the window of opportunity and sets the tone for a stable and prosperous adulthood. Therefore, a balanced Mental Condition is a foundation of the growth of maturity and later years of life. So, Mental Wellbeing of children is an important part for their growth and development. The Key purpose of this research is to examine the mental health problem in school going adolescence and children.